HIV induces synaptic hyperexcitation via cGMP-dependent protein kinase II activation in the FIV infection model. - Keira Sztukowski; Kaila Nip; Paige N Ostwald; Matheus F Sathler; Julianna L Sun; Jiayi Shou; Emily T Jorgensen; Travis E Brown; John H Elder; Craig Miller; Franz Hofmann; Sue VandeWoude; et al. (PLoS Biology)
Over half of individuals infected with human immunodeficiency virus (HIV) suffer from HIV-associated neurocognitive disorders (HANDs), yet the molecular mechanisms leading to neuronal dysfunction are poorly understood. Feline immunodeficiency virus (FIV) naturally infects cats and shares its structure, cell tropism, and pathology with HIV, including wide-ranging neurological deficits. We employ FIV as a model to elucidate the molecular pathways underlying HIV-induced neuronal dysfunction, in particular, synaptic alteration. Among HIV-induced neuron-damaging products, HIV envelope glycoprotein gp120 triggers elevation of intracellular Ca2+ activity in neurons, stimulating various pathways to damage synaptic functions. We quantify neuronal Ca2+ activity using intracellular Ca2+ imaging in cultured hippocampal neurons and confirm that FIV envelope glycoprotein gp95 also elevates neuronal Ca2+ activity. In addition, we reveal that gp95 interacts with the chemokine receptor, CXCR4, and facilitates the release of intracellular Ca2+ by the activation of the endoplasmic reticulum (ER)-associated Ca2+ channels, inositol triphosphate receptors (IP3Rs), and synaptic NMDA receptors (NMDARs), similar to HIV gp120. This suggests that HIV gp120 and FIV gp95 share a core pathological process in neurons. Significantly, gp95's stimulation of NMDARs activates cGMP-dependent protein kinase II (cGKII) through the activation of the neuronal nitric oxide synthase (nNOS)-cGMP pathway, which increases Ca2+ release from the ER and promotes surface expression of AMPA receptors, leading to an increase in synaptic activity. Moreover, we culture feline hippocampal neurons and confirm that gp95-induced neuronal Ca2+ overactivation is mediated by CXCR4 and cGKII. Finally, cGKII activation is also required for HIV gp120-induced Ca2+ hyperactivation. These results thus provide a novel neurobiological mechanism of cGKII-mediated synaptic hyperexcitation in HAND.